Interaction and Grammar: Predicative Adjective Constructions in English Conversation - Joan Bybee; Sandra A. Thompson (Languages, 2021)
This article studies the function of Copular Predicate Constructions in everyday English conversation. We compare predicate adjective constructions (PA) and constructions with a predicate nominal containing an adjective (PAN). We ask whether the attributive function of the adjective or the presence of a noun in the PAN leads to a difference in function in the two constructions. We propose that in most cases the adjective determines the function of the construction, leading to many parallels in usage between the PA and PAN constructions. A comparison with predicate nominal constructions (PN), in contrast, shows that not including an adjective in the constructions leads to a different set of meanings and implications. The conversational usage of these constructions provides evidence for a partial correspondence of form to function: Copular Predicate Constructions often constitute a complete turn in conversation, and if not a full turn, form their own prosodic units. Other properties of these constructions—the definiteness of the NP and the presence or absence of a N—correspond to different interactional work. A comparison of all three constructions shows that the adjective plays a determining interactional role, despite differences in syntactic configuration.